2012
DOI: 10.1111/j.1365-2109.2012.03109.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of night-time light intensity on the survival rate and stress responses in juvenile Pacific bluefin tunaThunnus orientalis(Temminck and Schlegel)

Abstract: Land‐based cultured juvenile Pacific bluefin tuna Thunnus orientalis (PBT) have high mortality rates due to collisions or contacts with tank walls after about 30 days of hatching. To determine the effect of night‐time lighting on their survival, juvenile PBT were reared under four different night‐time light intensities (0, 5, 15 and 150 lx) for 9 days, followed by a 3‐day observation period. High‐intensity, night‐time lighting (150 lx) significantly improved the survival rate (75.8%; P < 0.001) compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The main variables that are controlled in culturing fish are temperature and salinity. However, the manipulation of other factors such as light intensity and photoperiod are also important in fish production as they can optimize the production of a species as the physiological response of fish can be positively affected by variations in light intensity, wavelength and daily or seasonal photoperiod (Boeuf & Le Baile, 1999;Puvanendran & Brown, 2002;Stuart & Drawbridge, 2011;Gunnarsson et al, 2012;Prayogo et al, 2012;Honryo et al, 2013;Wang et al, 2015). Light intensity and photoperiod are also important factors in fish production as their manipulation can optimize the production of a species, as the behavior of fish can be positively affected by variations in light intensity, wavelength and daily or seasonal photoperiod (Boeuf & Le Baile, 1999;Puvanendran & Brown, 2002).…”
Section: ____________________mentioning
confidence: 99%
See 1 more Smart Citation
“…The main variables that are controlled in culturing fish are temperature and salinity. However, the manipulation of other factors such as light intensity and photoperiod are also important in fish production as they can optimize the production of a species as the physiological response of fish can be positively affected by variations in light intensity, wavelength and daily or seasonal photoperiod (Boeuf & Le Baile, 1999;Puvanendran & Brown, 2002;Stuart & Drawbridge, 2011;Gunnarsson et al, 2012;Prayogo et al, 2012;Honryo et al, 2013;Wang et al, 2015). Light intensity and photoperiod are also important factors in fish production as their manipulation can optimize the production of a species, as the behavior of fish can be positively affected by variations in light intensity, wavelength and daily or seasonal photoperiod (Boeuf & Le Baile, 1999;Puvanendran & Brown, 2002).…”
Section: ____________________mentioning
confidence: 99%
“…Light intensity and photoperiod are also important factors in fish production as their manipulation can optimize the production of a species, as the behavior of fish can be positively affected by variations in light intensity, wavelength and daily or seasonal photoperiod (Boeuf & Le Baile, 1999;Puvanendran & Brown, 2002). Most fish require a minimum level of light intensity, which allows visualization of the food, increases food intake and improves feed conversion leading to nutrients assimilation, it generates a faster and greater growth, improves the immune system, increases the enzyme activity and the accumulation of crude protein and lipids (Trippel & Neil, 2003;Monk et al, 2006;Sheng et al 2006;Ashley, 2007;Karakatsaouli et al, 2010;Stuart & Drawbridge, 2011;Honryo et al, 2013;Wang et al, 2015), while an inadequate light intensity can be stressful to fish and even lead to mortalities (Boeuf & Le Baile, 1999). The finding of a suitable photoperiod for a particular species, can reduce social stress and increases: food intake, nutrient assimilation and specific growth rate (Fielder et al, 2002;Trippel & Neil, 2002;Howell et al, 2003;Imsland et al, 2006;Ballagh et al, 2008;Martínez-Cárdenas & Purser, 2011;Gunnarsson et al, 2012;Prayogo et al, 2012).…”
Section: ____________________mentioning
confidence: 99%
“…The cortisol and glucose concentrations in whole bodies and plasma were measured using enzyme immunoassay (EIA) and glucose CII test kits (Wako Pure Chemical Industries Ltd., Osaka, Japan) and previously published methods (Ishibashi et al , Honryo et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have suggested that the rapid change of light intensity during the dawn period could be another cause of collision death (Masuma et al ; Fukuda et al ). We previously reported that nighttime lighting must be greater than 150 lx and that the survival rate of PBT juveniles cultured under 15 lx lights was poor in comparison to that of PBT juveniles raised in the natural photo environment (Honryo et al , Ishibashi et al ). Even if the retinomotor response of PBT juveniles under lighting that is more intense than 15 lx is considered to be photopic vision (Masuma et al ; Torisawa et al ), the fish swimming behaviors are irregular and unsuitable for survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation